Βιβλιοκρισία του: R. GOUNELLE (ed.), Les recensions byzantines de l’Évangile de Nicodème [Corpus Christianorum. Series apocryphorum, Instrumenta 3], Turnhout, Brepols 2008 - ΛΑΜΠΑΚΗΣ, Στυλιανός (Byzantina Symmeikta, 2010)
Βιβλιοκρισία του: R. Gounelle, Les recensions byzantines de l’Évangile de Nicodème [Corpus Christianorum. Series apocryphorum, Instrumenta 3], Turnhout, Brepols 2008, σσ. 332, ΙSΒΝ 978-2-503-52813-7.